2021
DOI: 10.1101/2021.04.26.441560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing the Tea Bag Index as a potential indicator for assessing litter decomposition in aquatic ecosystems

Abstract: The Tea Bag Index (TBI) approach is a standardized method for assessing litter decomposition in terrestrial ecosystems. This method allows determination of the stabilized portion of the hydrolysable fraction during the decomposition process, and derivation of a decomposition constant (k) using single measurements of the mass-loss ratios of green and rooibos teas. Although this method is being applied to aquatic systems, it has not been validated in these environments, where initial leaching tends to be higher … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…As discussed above, our results for the limestone site combined with the report by Mori, Ono, and Sakai (2021) suggest that the S of rooibos tea does not equal that of green tea. Because the two types of tea have different chemical compositions (Duddigan et al, 2020), we suggest that the S of rooibos tea is not always equal to that of green tea.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…As discussed above, our results for the limestone site combined with the report by Mori, Ono, and Sakai (2021) suggest that the S of rooibos tea does not equal that of green tea. Because the two types of tea have different chemical compositions (Duddigan et al, 2020), we suggest that the S of rooibos tea is not always equal to that of green tea.…”
Section: Resultssupporting
confidence: 80%
“…As the overturned assumption (i.e., S of rooibos tea equals that of green tea) may cause as much as a 20-times differences in the decomposition constant k (Mori, Ono, & Sakai, 2021), we suggest that the risk arising from the assumption should be considered, depending on the study purpose. Although the TBI was originally developed to obtain large-scale data with a simplified method (e.g., citizen science), the index was increasingly used in scientific research to clarify decomposition processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5b). This result agrees with previous studies performed in aquatic ecosystems, which demonstrated that rooibos tea had a larger S than green tea (Mori, 2021(Mori, , 2021c. Thus, the present study provides strong evidence for the assumptions in several previous studies: green tea and rooibos tea should have different S values because their chemical compositions are completely different (Mori et al, 2022(Mori et al, , 2021b.…”
Section: Resultssupporting
confidence: 93%
“…1b), suggesting that the second premise is not always true. In aquatic ecosystems, the decomposition constant k calculated by the TBI was much larger than those determined by fitting time-series data of rooibos tea decomposition to an asymptote model (Mori, 2021;Mori et al, 2021c), possibly due to quick loss of the soluble fraction in the aquatic ecosystem. It is essential to test the validity of the TBI in terrestrial ecosystems.…”
mentioning
confidence: 79%